Reconstructing Parents’ Meetings in Primary Schools: The Teacher as Expert, the Parent as Advocate and the Pupil as Self-Advocate - Gillian Inglis (University of Ljubljana, 2012)
The efficacy of parents’ meetings in primary schools in the UK is an area in need of research. This article uses an approach informed by grounded theory to explore the experiences and satisfaction of parents, teachers and pupils regarding bi-annual meetings to discuss pupil progress. A two-phase approach was utilised, with diary-interviews with parents and teachers and group pupil interviews in Phase 1, followed by a parents’ questionnaire in Phase 2 derived from Phase 1 data. The findings from a doctoral study provide an overall more positive depiction of these meetings compared to existing research in the secondary sector. A model of the teacher as the expert and information-giver persists, but a consumerist ideology appears evident as parents seek to participate and advocate on behalf of their child. As parents become more proactive and teachers act to retain their professional authority, the interaction of the professional and advocate has excluded the perspective of the child. This leaves pupils in search of self-advocacy at meetings in which they are the object of discussion, but cannot be present. While pupils generally favour involvement, adults express a protectionist perspective on pupil exclusion with exceptional factors indicated as being the age of the child and the content of the meeting.